Community Actions to Address Alcohol Problems: Lessons Learned - Kaewnuy, Suwara; Phakdeesettakun, Kannapon; Thamarangsi, Thaksaphon (Journal of Health Science of Thailand, 2017)
This research studied patterns and processes of alcohol policy community interventions in selected 13 good-practice communities. Qualitative techniques were employed through in-depth interviews and focus group discussions with key informants from these communities. It was found that the ignition of community interventions was largely driven by the linkage between these community and alcohol policy movements and impacts at macro scale, as well as by community concern on alcohol-related problems. Many similarities in the policy process of the studies communities were identified, which allowed a synthesis of major supportive factors and settings for successful community actions. These were relevant to local culture and context, starting from the easy-to-win battles which could produce concrete positive outcome, connecting with policy movements at larger scales, setting networks, creating knowledge sharing mechanisms, creating incentive system, integration with other sectors and topics, and most of all, platforms for extensive participation. The process of these good practices showed the extensive involvement and ownership of local people to the alcohol policy intervention in every stage; from problem structuring, creating collective commitment, planning, endorsing community rules with consensus, implementation, to monitoring and evaluation. This study confirms that three mechanisms and processes are crucial for the success and sustainability of these interventions. These are mechanisms and processes to build up community involvement, to build up strong linkage with actors and movements outside community, and to create knowledge management infrastructures and means.